Enzymatic hydrolyzed preparation of Saccharomyces cerevisiae: an additive with antibacterial potential for animal feeding - Rodríguez, Marlen; Milián, Grethel; Rondón, Ana J.; Bocourt, R.; Laurencio, Marta; Portilla, Yadileiny; Beruvides, A. (Cuban Journal of Agricultural Science, 2016)
In order to evaluate the antibacterial potential of an enzymatic hydrolyzed preparation of Saccharomyces cerevisiae, three in vitro experiments were performed. The confrontation of the biopreparation with the pathogenic microorganisms was performed through the methods of substance diffusion in agar, the co-culture establishment and the co-aggregation technique. Bacterial isolations were taken from the liver of sick chicken, and were isolated and identified at the Laboratorio de Investigación y Diagnóstico Aviar (LIDA) in Matanzas. It was demonstrated that the hydrolyzed preparation contains antibacterial substances, mainly bacteriocins and/or antibiotics, which inhibit the growth of Klebsiella spp., Streptococcus spp., Staphylococcus spp., Salmonella spp. and E. coli spp. The antibacterial effect of this additive was demonstrated after decreasing the population of pathogenic bacteria, when they are cultivated in the same medium. The strains of Salmonella spp. and E. coli spp. induce the ability of co-aggregation (32.7 and 22.3 %, respectively) to the components of the cell wall of yeasts within the hydrolyzed preparation. Results indicate the limited growth of bacterial strains in the presence of the enzymatic hydrolyzed preparation of yeast. This activity is multifactorial and unleashes different processes that are interrelated and, as a consequence, favor the improvements of physiology, yield and health of animals. Therefore, it can be used as an additive for animal feeding. Key words: enzymatic hydrolyzed preparation, antibacterial activity, co-aggregation, pathogenic bacteria